Evidence-based nursing : a guide to clinical practice - 4 0 16; Guyatt, Gordon.;Ciliska, Donna; 5 (St. Louis, Missouri : Elsevier Mosby, 2005)
Accompanying CD-ROM has the full text of the book in electronic format with linking, classification, and coding, with filtering, keyword searching, and the option to rearrange content.
Ch. 1: Introduction to Evidence-Based Nursing -- Ch. 2: Finding the Evidence -- Ch. 3: Health Care Interventions and Harm: An Introduction -- Ch. 4: Health Care Interventions -- Ch. 5: Harm -- Ch. 6: Diagnosis -- Ch. 7: Prognosis -- Ch. 8: Qualitative Research -- Ch. 9: Summarizing the Evidence Through Systematic Reviews -- Ch. 10: Moving from Evidence to Action Using Clinical Practice Guidelines -- Ch. 11: Changing Nursing Practice in an Organization -- Ch. 12: Quality of Life -- Ch. 13: Surrogate Outcomes -- Ch. 14: Surprising Results of Randomized Controlled Trials -- Ch. 15: The Principle of Intention-to-Treat -- Ch. 16: When to Believe a Subgroup Analysis -- Ch. 17: Health Services Interventions -- Ch. 18: Economic Evaluation -- Ch. 19: Computer Decision Support Systems -- Ch. 20: Clinical Manifestations of Disease -- Ch. 21: Differential Diagnosis -- Ch. 22: Clinical Prediction Rules -- Ch. 23: Publication Bias -- Ch. 24: Evaluating Differences in Study Results -- Ch. 25: Fixed-Effects and Random-Effects Models -- Ch. 26: Bias and Random Error -- Ch. 27: Measures of Association -- Ch. 28: Hypothesis Testing -- Ch. 29: Confidence Intervals -- Ch. 30: Measuring Agreement Beyond Chance -- Ch. 31: Regression and Correlation -- Ch. 32: Number Needed to Treat -- Ch. 33: Applying Results to Individual Patients -- Ch. 34: Incorporating Patient Values -- Ch. 35: Interpreting Levels of Evidence and Grades of Health Care Recommendations -- Ch. 36: Recommendations about Screening.
certifiednurseeducator.
Includes bibliographical references and index.
System requirements: Either Windows 98 or higher or Mac OS X or later; Internet Explorer 5.5 or later and Adobe Reader 6.0 or higher.
Keywords: 2 -- 0; 6; Evidence-based nursing. -- 20; 20; 2